Trans-ethnic study confirmed independent associations of HLA-A02:06 and HLA-B44:03 with cold medicine-related Stevens-Johnson syndrome with severe ocular surface complications - Ueta, Mayumi; Kannabiran, Chitra; Wakamatsu, Tais Hitomi; Kim, Mee Kum; Yoon, Kyung-Chul; Seo, Kyoung Yul; Joo, Choun-Ki; Sangwan, Virender; Rathi, Varsha; Basu, Sayan; Shamaila, Almas; Lee, Hyo Seok; et al. (Scientific reports, 2014)
Stevens-Johnson syndrome (SJS) and its severe variant, toxic epidermal necrolysis (TEN), are acute inflammatory vesiculobullous reactions of the skin and mucous membranes. Cold medicines including non-steroidal anti-inflammatory drugs and multi-ingredient cold medications are reported to be important inciting drugs. Recently, we reported that cold medicine related SJS/TEN (CM-SJS/TEN) with severe mucosal involvement including severe ocular surface complications (SOC) is associated with HLA-A*02:06 and HLA-B*44:03 in the Japanese. In this study, to determine whether HLA-B*44:03 is a common risk factor for CM-SJS/TEN with SOC in different ethnic groups we used samples from Indian, Brazilian and Korean patients with CM-SJS/TEN with SOC and investigated the association between CM-SJS/TEN with SOC and HLA-B*44:03 and/or HLA-A*02:06 . We found that HLA-B*44:03 was significantly associated with CM-SJS/TEN with SOC in the Indian and Brazilian but not the Korean population and that HLA-A*02:06 might be weakly associated in the Korean- but not the Indian and Brazilian population.